Analisis Pengaruh Upah, Jumlah Tenaga Kerja, dan Infrastruktur Jalan Terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Alexander, Alexander; Yulmardi, Yulmardi; Edi, Jaya Kusuma (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
The study is entitled Analysis of the Impact of Wages, Number of Labor, and Road Infrastructure on Economic Growth in Jambi Province. The purpose of this research is to know the development of Wages, the amount of Labor, and Road Infrastructure on Economic Growth in Jambi Province and to know the influence of Wages, Total Manpower, and Road Infrastructure on Economic Growth in Jambi Province.